Nursery Production of Neltuma Genus in Arid and Semiarid Regions of Argentine: a Review - Massa Decon, Anabella Mirtha; Pérez, Silvina (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
Neltuma spp. (previously known as Prosopis spp.) are vital for ecological restoration and sustainable forestry in arid and semiarid environments. Although extensively studied, nursery techniques are still inconsistently applied, and poorly integrated. This review synthesizes recent scientific advances in seedling cultivation under controlled conditions, focusing on seed source selection, dormancy-breaking treatments, and substrate-container interactions. This review incorporates developments concerning seed source selection, plant physiology, and nursery trials to identify knowledge gaps and propose strategies for reforestation improvement. We offer actionable guidance for nursery operators, restoration professionals, and policymakers. Future research should focus on long-term field studies, genomic tools, standardization of nursery techniques, biological interactions that improve stress tolerance, and economic feasibility, especially for under-researched species. Highlights: A comprehensive review of nursery production techniques for Neltuma spp. in arid and semi-arid regions of Argentina. Genetic variation and seed provenance significantly influence seedling performance and restoration success. Species-specific pre-germinative treatments improve germination rates and uniformity in nursery settings. Container–substrate combinations strongly affect morphological traits such as height, root collar diameter, and biomass. Future research should prioritize microbial inoculants, cost–benefit analyses, and long-term field evaluations to develop scalable nursery protocols.